The Direct Costs of Microsurgical Resection of Vestibular Schwannomas. Issue 3 (March 2020) - Saliba, Joe; Mohammadzadeh, Amir; Tawfik, Kareem O.; Carriere, Junie S.; Schwartz, Marc S.; Nguyen, Quyen T.; Friedman, Rick A.
Abstract : Objective: To determine and itemize surgical costs associated with the translabyrinthine (TL), retrosigmoid (RS), and middle cranial fossa (MCF) approaches for microsurgical excision of vestibular schwannoma (VS). Study Design: Retrospective cost analysis study. Setting: Tertiary referral center. Patients: Thirty consecutive adult patients underwent microsurgical excision of VS by either TL, RS, or MCF approach (10 per approach). Interventions: Microsurgical excision of VS by one of the three major approaches. Medical and financial data were collected. Main Outcome Measures: Total operating room time (minutes), skin-to-skin time (minutes), operating room cost ($US), and surgical supplies cost ($US). Results: The MCF approach was associated with the shortest skin-to-skin time (230.3 min, p  < 0.001). Mean overall nonsurgical room time was 94.7 minutes and not significantly different among approaches ( p  = 0.55). Mean total surgical supplies cost was $5, 028 and was the highest for the RS ($7, 116; p  < 0.001) but not significantly different between TL and MCF. Mean operating room services charges were $68, 417 overall and were the lowest for the MCF group ($53, 306; p  = 0.01). Tumor size was not correlated with surgical supplies cost ( p  = 0.74). The items associated with the highest average cost per case were the surgical aspirator ($1, 062), drill burs ($928), and titanium implants ($575). There was redundancy in multiple surgical items such as drill burs, hemostatic agents, and sutures. Conclusion: This study is the first to provide a detailed itemization of the surgical expenses specific to VS resection. Elevated nonsurgical room time and supply redundancy provides the opportunity for decreasing surgical costs and waste.